Molecular Analysis of a Saccharomyces cerevisiae Mutant with Improved Ability To Utilize Xylose Shows Enhanced Expression of Proteins Involved in Transport, Initial Xylose Metabolism, and the Pentose Phosphate Pathway - Wahlbom, C. Fredrik (American Society for Microbiology, 2003)
Differences between the recombinant xylose-utilizing Saccharomyces cerevisiae strain TMB 3399 and the mutant strain TMB 3400, derived from TMB 3399 and displaying improved ability to utilize xylose, were investigated by using genome-wide expression analysis, physiological characterization, and biochemical assays. Samples for analysis were withdrawn from chemostat cultures. The characteristics of S. cerevisiae TMB 3399 and TMB 3400 grown on glucose and on a mixture of glucose and xylose, as well as of S. cerevisiae TMB 3400 grown on only xylose, were investigated. The strains were cultivated under chemostat conditions at a dilution rate of 0.1 h(−1), with feeds consisting of a defined mineral medium supplemented with 10 g of glucose liter(−1), 10 g of glucose plus 10 g of xylose liter(−1) or, for S. cerevisiae TMB 3400, 20 g of xylose liter(−1). S. cerevisiae TMB 3400 consumed 31% more xylose of a feed containing both glucose and xylose than S. cerevisiae TMB 3399. The biomass yields for S. cerevisiae TMB 3400 were 0.46 g of biomass g of consumed carbohydrate(−1) on glucose and 0.43 g of biomass g of consumed carbohydrate(−1) on xylose. A K(s) value of 33 mM for xylose was obtained for S. cerevisiae TMB 3400. In general, the percentage error was <20% between duplicate microarray experiments originating from independent fermentation experiments. Microarray analysis showed higher expression in S. cerevisiae TMB 3400 than in S. cerevisiae TMB 3399 for (i) HXT5, encoding a hexose transporter; (ii) XKS1, encoding xylulokinase, an enzyme involved in one of the initial steps of xylose utilization; and (iii) SOL3, GND1, TAL1, and TKL1, encoding enzymes in the pentose phosphate pathway. In addition, the transcriptional regulators encoded by YCR020C, YBR083W, and YPR199C were expressed differently in the two strains. Xylose utilization was, however, not affected in strains in which YCR020C was overexpressed or deleted. The higher expression of XKS1 in S. cerevisiae TMB 3400 than in TMB 3399 correlated with higher specific xylulokinase activity in the cell extracts. The specific activity of xylose reductase and xylitol dehydrogenase was also higher for S. cerevisiae TMB 3400 than for TMB 3399, both on glucose and on the mixture of glucose and xylose.